2019
DOI: 10.1108/pm-05-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

What is determining affordable housing shortages in the Greater Kuala Lumpur, Malaysia?

Abstract: Purpose The purpose of this paper is to investigate the determinants of the affordable housing shortage in the Greater Kuala Lumpur from the suppliers’ perspectives. Design/methodology/approach Primary data were collected through a cross-sectional survey questionnaire comprising 21 determinants and 111 experts in the housing industry. Findings The affordable housing shortages are consequences of regulations and policies on land allocations, building materials and the affordable housing market. The governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…This is consistent with the central limit theorem (CLT). Based on the CLT principle, the distribution of sample means approximates a normal distribution as the sample size increases (Olanrewaju and Idrus, 2020). For the CLT principle to be valid, a sample size of 30 or more is statistically required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the central limit theorem (CLT). Based on the CLT principle, the distribution of sample means approximates a normal distribution as the sample size increases (Olanrewaju and Idrus, 2020). For the CLT principle to be valid, a sample size of 30 or more is statistically required.…”
Section: Methodsmentioning
confidence: 99%
“…This research identified, prioritized and categorized the causes and remedies. Categorizing the causes and remedies will help streamline and enhance decisionmaking on the performance of construction operations (Olanrewaju and Idrus, 2020). Analyses of interactions between causes and remedies pose a clustering problem due to the lack of labelling in the data.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“… Araya, 2021b , Brundtland et al, 1987 , Clemente-Suá rez et al, 2021 , Cleveland Clinic, 2020 , de Bruin et al, 2020 , Dí az-Soler et al, 2019 , Fadilllah, 2020c , Gul and Ak, 2018 , Hinton, 2014 , Hwang and Kim, 2011 , Jonathan, 2020 , Liang et al, 2018 , Lingard et al, 2021 , Lu et al, 2020 , Muhyiddin, 2020 , Nawaz et al, 2019 , New Straits Times, 2020a , New Straits Times, 2020b , New Straits Times, 2020c , New Straits Times, 2020d , Occupational Safety and Health Administration, 2020 , Olanrewaju and Idrus, 2020 , Sadarangani et al, 2017 , Sarwar et al, 2020 , Spiegel and Meadows, 2010 , The World Bank, 2020 , Tong et al, 2018 , Wang et al, 2019 , Zhang and Mohandes, 2020 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…The central limit theorem (CLT) proves this. The CLT principle states that as sample size increases, the sample mean distribution approaches a normal distribution (Olanrewaju and Idrus, 2020). For the CLT principle to be valid, a sample size of 30 or greater is statistically required.…”
Section: Methodsmentioning
confidence: 99%